2019
DOI: 10.4269/ajtmh.19-0309
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Dengue, Chikungunya, and Zika Virus Disease in U.S. States and Territories, 2017

Abstract: Dengue, chikungunya, and Zika viruses, primarily transmitted by Aedes species mosquitoes, have caused large outbreaks in the Americas, leading to travel-associated cases and local mosquito-borne transmission in the United States. We describe the epidemiology of dengue, chikungunya, and noncongenital Zika virus disease cases reported from U.S. states and territories in 2017, including 971 dengue cases, 195 chikungunya cases, and 1,118 Zika virus disease cases. Cases of all three diseases reported from the terri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 37 publications
(44 reference statements)
0
26
0
Order By: Relevance
“…From 2005 to 2015, annual rainfall ranged from 297 to 381 cm and average temperature was between 27.3-28.5 °C [1]. The wet tropical environment and resulting high density of mosquitoes [19] leads to high risk of vector-borne diseases; dengue seroprevalence was over 95% in 2010 [20] and there are frequent outbreaks of arboviral diseases [21,22]. The population, estimated at 61,181 in 2014 [1] declined between 2000 and 2010 at an estimated annual rate of − 3.1%.…”
Section: Study Locationmentioning
confidence: 99%
“…From 2005 to 2015, annual rainfall ranged from 297 to 381 cm and average temperature was between 27.3-28.5 °C [1]. The wet tropical environment and resulting high density of mosquitoes [19] leads to high risk of vector-borne diseases; dengue seroprevalence was over 95% in 2010 [20] and there are frequent outbreaks of arboviral diseases [21,22]. The population, estimated at 61,181 in 2014 [1] declined between 2000 and 2010 at an estimated annual rate of − 3.1%.…”
Section: Study Locationmentioning
confidence: 99%
“…The former studies were mainly centered on the prevention and control of diseases, i.e., malaria, H1N1 flu, dengue, AIDS, Chikungunya, and Zika (Saha and Samanta 2019 ; Vairo et al 2019 ; Hausman et al 2020 ; Kaur et al 2021 ; Wang et al 2021 ). Among them, the first array of studies considered the epidemiology of diseases (Adams et al 2019 ; Mosnier et al 2019 ; Cissoko et al 2020 ). The second batch of studies focused on conducting surveys to find the impact of certain factors on the prevention of epidemic (Preti et al 2020 ; Wenjun et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…This is concerning because we and others have demonstrated that antibodies elicited by WNV are cross-reactive to ZIKV, suggesting that preexisting WNV immunity has the potential to impact ZIKV pathogenesis (31,39,40). In fact, during the 2016 outbreak, mosquito transmission of ZIKV occurred in both Texas and Florida, demonstrating the potential for ZIKV to expand into WNV-endemic areas (41). This risk is expected to increase as global temperatures rise (42).…”
Section: Introductionmentioning
confidence: 97%